Phytochemical study and antioxidant activity of the most used medicinal and aromatic plants in Morocco. Issue 2 (4th March 2022) - Ben Bakrim, W.; Aghraz, A.; Hriouch, F.; Larhsini, M.; Markouk, M.; Bekkouche, K.; Costa, R.; Arrigo, S.; Cicero, N.; Dugo, G.
ABSTRACT: Genus Mentha is represented in Morocco by 10 species including hybrids. The species of this genus are used as herbal teas and condiments, due to their distinct aroma. In this study, infusions of the fresh aerial parts of three Mentha spp., commonly cultivated and used in Morocco, were evaluated for phenolic contents and antioxidant activity. Antioxidant capacity was assessed by three tests: scavenger activity by DPPH, FRAP (Ferric Reducing Antioxidant Power), and β-carotene bleaching methods. Infusions of M. piperita possess the best ability to reduce DPPH and chelate iron (IC50  = 7.50 ± 0.19 and 5.84 ± 0.36 μg/mL, respectively), while M. spicata shows great efficiency on inhibiting β-carotene (IC50  = 62.67 ± 0.01 μg/mL). The antioxidant capacity was significantly correlated with the total phenolic content and HPLC chromatographic analyses showed the predominance of phenolic acids, especially rosmarinic acid. Furthermore, by GC-MS analysis of Mentha spp. essential oils, eucalyptol, limonene, carvone, and pulegone were identified as predominant components.